RESEARCH REPORT - Armstrong, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This paper asks you to identify a current ethical dilemma in medicine that interests you and research it. You should use the sociological concepts and insights you have gained about health and medicine in this class to set the ethical issue or problem in a broader social context.